2004
DOI: 10.7326/0003-4819-141-11-200412070-00007
|View full text |Cite
|
Sign up to set email alerts
|

Negative d-dimer Result To Exclude Recurrent Deep Venous Thrombosis: A Management Trial

Abstract: Measurement of plasma d-dimer by using the automated quantitative assay STA-Liatest D-di seems to provide a simple method for excluding acute recurrent DVT in symptomatic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
1
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 25 publications
1
47
1
3
Order By: Relevance
“…It ensues from these findings that DD should only be ordered for patients in whom DVT is deemed unlikely, since DD results do not alter the diagnostic approach in the rest. The number of patients enrolled is limited but close to that reported by Rathbun et al [5] assuming individuals on warfarin would not have been considered; prevalence of DVT in our series is higher (44.8 vs. 33%), but exclusion of patients on OAT with lower confirmation rates (about 13% [13]) might partly justify these differences.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…It ensues from these findings that DD should only be ordered for patients in whom DVT is deemed unlikely, since DD results do not alter the diagnostic approach in the rest. The number of patients enrolled is limited but close to that reported by Rathbun et al [5] assuming individuals on warfarin would not have been considered; prevalence of DVT in our series is higher (44.8 vs. 33%), but exclusion of patients on OAT with lower confirmation rates (about 13% [13]) might partly justify these differences.…”
Section: Discussionsupporting
confidence: 76%
“…Some 15% of patients (24.6% of this later clinical probability group) could be safely discharged without the need of any diagnostic tests; the follow-up period was uneventful in all of them. This proportion is clearly lower to that reported by Rathbun et al [5] (45%); even if patients using oral anticoagulants had been excluded it would have been 36%. To a good extent the remarkably higher mean age of our series of patients (71 vs. 55) might be responsible for these differences, since DD levels tend to increase with aging [14].…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…Five prospective cohort management studies have reported results for strategies involving D-dimer testing in patients with suspected recurrent DVT. 19,[47][48][49][50] In a randomized trial of 1,096 outpatients with suspected DVT, of whom 102 had prior VTE, 19 the combination of an unlikely pretest probability (using the modified Wells model, which includes a history of previous VTE as one of the factors used to determine clinical probability) and negative D-dimer (either moderate or high sensitivity) had a frequency of VTE during 3-month follow-up of 0.9% (95% CI, 0.3 to 3.3%); however, results for the 102 patients with suspected recurrence were not presented separately. In two studies in which a negative sensitive D-dimer was used either in combination with an unlikely pretest probability using the modified Wells model 48 or a compression ultrasound at presentation that was either normal or showed an increase in residual diameter of less than 4 mm 49 to exclude recurrence, no patients experienced VTE during 3 months of follow-up.…”
Section: • Myocardial Infarctionmentioning
confidence: 99%